Randomised trial of three rapamycin-eluting stents with different coating strategies for the reduction of coronary restenosis: 2-year follow-up results. Issue 18 (9th July 2009) - Byrne, R A; Kufner, S; Tiroch, K; Massberg, S; Laugwitz, K-L; Birkmeier, A; Schulz, S; Mehilli, J
Abstract : Background: Drug-eluting stent (DES) platforms devoid of durable polymer have potential to enhance long-term safety outcomes. The ISAR-TEST-3 study was a randomised trial comparing three rapamycin-eluting stents with different coating strategies. The present study examined 2-year outcomes of these patients and is the first large-scale trial to report longer-term outcomes with biodegradable polymer and polymer-free DES. Methods: Patients with de novo coronary lesions in native vessels were randomly assigned to receive biodegradable polymer (BP; n = 202), permanent polymer (PP; Cypher; n = 202) and polymer-free (PF; n = 201) stents. The 2-year endpoints of interest were target lesion revascularisation (TLR), death/myocardial infarction (MI), stent thrombosis and delayed angiographic late luminal loss (LLL) between 6–8 months and 2 years. Results: There were no significant differences in TLR (8.4%, 10.4% and 13.4% for BP, PP and PF stents, respectively; p = 0.19), death/MI (5.9%, 6.4% and 6.5% with BP, PP and PF respectively; p = 0.97) or stent thrombosis (definite/probable 0.5%, 1.0% and 1.0% with BP, PP and PF, respectively; p = 0.82). Paired angiographic follow-up at 6–8 months and 2 years was available for 302 patients (69.0% of eligible patients). Delayed LLL was significantly different across the treatment groups: 0.17 (0.42) mm, 0.16 (0.41) mm and −0.01 (0.36) mm for BP, PP and PF stents, respectively (p<0.001). Conclusion: Clinical antirestenotic efficacy was maintained with all three platforms between 1 and 2 years, although angiographic surveillance showed ongoing delayed LLL with both BP and PP stent platforms. At 2 years there was no signal of a differential safety profile between the three stent platforms.